Estimating Economic Returns of Sheep and Goat Rearing in Karak Governorate - Bdour , Mohammed Ali; Zyadeen , Ayman Frid; Alkawalit , Nayl Twfiq (Jordan Journal of Agricultural Sciences, 2023)
This study aims to estimate the economic returns of sheep and goat rearing as well as total cost and returns to identify the profit margin made by out each farmer. The random sample consists of 196 breeders who breed 58240, sheep and goats in the Karak governorate of Jordan. The sample represents 13% of the total sheep and goat population (445300) in Karak. The primary data were collected through personal interviews with farmers using a questionnaire. The questionnaire was designed to achieve the study objectives and consisted of three themes. The first theme was questioning the variables that relate to the farmer’s personal characteristics (demography). The second theme contains a set of questions regarding financial production cost and return parameters during the milking season including the marketing process. The third theme consists of information about the return from selling individual sheep and goats and products such as wool and manure. The collected data from the questionnaire were statistically analyzed following Likert 5 Scale The financial analysis was conducted using Gross margin analysis. The findings of the analysis show that 52.6% of farmers were above 50 years old. the average size of the herd was 297. The variable cost for the herd was 13067.98, Jordanian Dinar, while the total returns were 17104.54, JOD, and the Gross margin ratio was 0.23599. The amount of milk production was (3,494.4) tons in a season lasting 3 months on average. The average prices of milk of goats and sheep are 1.1 and 0.87 JOD/kg, respectively, Moreover, 53.3% of the farmers processed the domestically produced milk into Jameed, butter, and margarine. The result of the analysis of gross margin was 30%, indicating the sheep and goats rearing projects make profits in Karak Governorate. The study recommends that a national program should be developed to maintain local breeds, set appropriate standards, and define trademarks for the local production of Jameed and domestic margarine.